2013
DOI: 10.1017/s0007114512006095
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract triggers apoptosis in Caco-2 human colon cancer cells through reactive oxygen species and calcium increase: extracellular signal-regulated kinase involvement

Abstract: Grape seed extract (GSE) from Italia, Palieri and Red Globe cultivars inhibits cell growth and induces apoptosis in Caco-2 human colon cancer cells in a dose-dependent manner. In order to investigate the mechanism(s) supporting the apoptotic process, we analysed reactive oxygen species (ROS) production, intracellular Ca 2þ handling and extracellular signal-regulated kinase (ERK) activation. Upon exposure to GSE, ROS and intracellular Ca 2þ levels increased in Caco-2 cells, concomitantly with ERK inactivation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Intracellular ROS production was monitored by adding the 2',7'-dichlorodihydrofluorescein diacetate (H 2 -DCF-DA, Sigma Aldrich), according to Dinicola et al 27 , in Caco-2 cells exposed to oxidized cholesterol (75 μg/mL) in complete medium and incubated for 0-180 15 min and in cells pretreated with the tested phenolic compounds (5-25 µM in water solution, 30 min), prior to exposure to oxidized cholesterol (75 μg/mL for 30 min), with some modifications. After incubation the culture medium was replaced with PBS and cells were loaded with 10 µM H 2 -DCF-DA for 30 min.…”
Section: Ros Production In Caco-2 Cellsmentioning
confidence: 99%
“…Intracellular ROS production was monitored by adding the 2',7'-dichlorodihydrofluorescein diacetate (H 2 -DCF-DA, Sigma Aldrich), according to Dinicola et al 27 , in Caco-2 cells exposed to oxidized cholesterol (75 μg/mL) in complete medium and incubated for 0-180 15 min and in cells pretreated with the tested phenolic compounds (5-25 µM in water solution, 30 min), prior to exposure to oxidized cholesterol (75 μg/mL for 30 min), with some modifications. After incubation the culture medium was replaced with PBS and cells were loaded with 10 µM H 2 -DCF-DA for 30 min.…”
Section: Ros Production In Caco-2 Cellsmentioning
confidence: 99%
“…GSE induced apoptosis and increase in ROS and Ca 2+ levels in Caco-2 colon cancer cells and this was accompanied by inactivation of extracellular signalregulated kinase (ERK). Cotreatment of Caco-2 cells with antioxidant, N-acetyl cysteine and calcium chelator ethylene glycol tetraacetic acid suppressed GSE-induced apoptosis and ERK inactivation indicating a critical role of ROS in the anticarcinogenic activity of GSE [32]. Another study demonstrated a synergistic effect between (−)-epigallocatechin-3-gallate, vitexin-2-O-xyloside and raphasatin (4-methylsulphanyl-3-butenyl isothiocyanates) on growth inhibition in LoVo and CaCo-2 colon cancer cells.…”
Section: Ros and Cancer Therapymentioning
confidence: 99%
“…Previous reports have shown that the ERK1/2 signaling pathway is activated during oxidative stress and that ERK1/2 phosphorylation plays a key role in mediating cell survival/cell death, depending on stimulus duration and cell type 41, 42. This dual role of the ERK1/2 signaling pathway has also been observed in OLs.…”
Section: Discussionmentioning
confidence: 74%